2022
DOI: 10.1002/cjoc.202100438
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stereoselective C‐Glycosylation by Photocatalytic Decarboxylative Alkynylation on Anomeric Position: A Facile Access to Alkynyl C‐Glycosides

Abstract: The highly stereoselective synthesis of diverse medicinally valuable alkynyl C-glycosides under mild and green reaction conditions remains a great challenge. Herein, we wish to report a visible-light induced photocatalytic decarboxylative alkynylation approach. By utilizing an iridium photocatalyst in the presence of visible light, glycosyl radicals are in-situ generated via the decarboxylation of anomeric acids and efficiently coupled with a variety of ethynylbenziodoxolones (EBXs), which allows the facile sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 42 publications
(1 reference statement)
0
17
0
Order By: Relevance
“…More importantly, Mes-Acr + -catalyzed decarboxylative fluorination enables the synthesis of RGFs 2r–u from benzyl- or benzoyl-protected gluco- and galactopyranuronic acids 1r–u , typical hexopyranuronic acids which are relatively underexplored. 12,13 We found that protecting groups have paramount influence on the decarboxylative fluorination of hexose-based pyranuronic acids. Specifically, Bn-protected glucuronic acids 1r and 1s with either an α-methoxy or β-substituent at the anomeric position furnished the respective RGFs 2r and 2s in 63% and 72% yields with identical stereoselectivities.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…More importantly, Mes-Acr + -catalyzed decarboxylative fluorination enables the synthesis of RGFs 2r–u from benzyl- or benzoyl-protected gluco- and galactopyranuronic acids 1r–u , typical hexopyranuronic acids which are relatively underexplored. 12,13 We found that protecting groups have paramount influence on the decarboxylative fluorination of hexose-based pyranuronic acids. Specifically, Bn-protected glucuronic acids 1r and 1s with either an α-methoxy or β-substituent at the anomeric position furnished the respective RGFs 2r and 2s in 63% and 72% yields with identical stereoselectivities.…”
Section: Resultsmentioning
confidence: 91%
“…These unique diastereoselectivities are attributed to the stability of α-oxyalkyl radicals arising from the n–p c interaction between the n orbital of the lone electron pair of endocyclic oxygen and the p orbital of the C-4 radical as well as from the quasi-homo anomeric effect between the σ* orbital of O-3 and C-4 radicals. 12,20 In addition, it should be noted that 1f was converted into 2f in 30% yield with Cs 2 CO 3 as the base instead of CsHCO 3 . This result demonstrated the important role of CsHCO 3 in decarboxylative fluorination of uronic acids bearing protecting groups susceptible to the base.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, they can be used as coupling reagents for biological probes 2 and for the synthesis of oligosaccharides via multi-component reactions. 3 They are also valuable intermediates employed in C–H activation, 4 radical reactions, 5 and the Liebeskind–Srogl reaction 6 for the synthesis of C -glycosides. 7…”
mentioning
confidence: 99%
“…7 b , 19 Recently, glycosyl carboxylic acids have been frequently utilized as radical precursors in decarboxylative C -glycosylation. 5 However, uniformly protected substrates were usually used. With differently O-5 protected furanosyl acids in hand, we thought it was worthwhile to probe the effect of the protecting group, as shown in Zhang's work.…”
mentioning
confidence: 99%